PENGEMBANGAN SISTEM INFORMASI ABSENSI BERBASIS WEB MOBILE DALAM MENINGKATKAN KEDISIPLINAN DAN KARAKTER SISWA DI SMP NEGERI 1 PRINGSEWU - Asiyani, Lusi; Suyono, Suyono; Mazdayani, Mazdayani (JECE (Journal of Ethics and Character Education), 2025)
The development of information technology in education has encouraged schools to implement more effective and efficient administrative systems, including student attendance management. SMP Negeri 1 Pringsewu still uses a manual attendance system which has several weaknesses, such as delays in data processing, risk of data loss, and ineffective monitoring of student discipline. This study aims to develop a web mobile-based attendance information system to improve attendance management effectiveness and support the enhancement of student discipline and character building. The research method used was Research and Development (R&D) with data collection techniques including observation, interviews, and literature studies. System testing was conducted on 61 respondents consisting of 2 teachers, 1 administrative staff member, 3 homeroom teachers, and 55 students using a Likert scale questionnaire. The results showed that the system achieved a success rate of 87% categorized as very good. The usability aspect obtained 90%, data accuracy 88%, monitoring effectiveness 86%, improvement in student discipline 84%, and character strengthening 83%. The web mobile-based attendance system was considered capable of assisting schools in managing student attendance in real time while supporting the development of discipline and responsibility among students in a sustainable manner.